Pengaruh Spiritual Emotional Freedom Technique (Seft) Terhadap Penurunan Kadar Gula Darah Penderita Diabetes Mellitus Tipe 2 Di RSUD Kota Surakarta - Ros Endah Happy Patriyani; Sunarsih Rahayu (Interest : Jurnal Ilmu Kesehatan, 2018)
Backgound: The incidence and severity levels of Diabetes Mellitus (DM) can be reduced through life style modification. The nurses’ ability in complementary modalities can help the patients to modify their life style by managing the stress levels; doing standard medical cares to help reducing and controlling blood sugar levels. One form of complementary modalities is SEFT. SEFT is one relaxation technique that can reduce anxiety and optimally reduce blood sugar level. Relaxation can affect hypothalamus to regulate and decrease the activity of the sympathetic nervous system. The purpose of this research is to find out the impact of SEFT to the decrease blood sugar levels on type 2 DM patients. Method: The method applied in the research was quasi-experimental pre-posttest with control group. The research population was 100 type 2 DM patients (50 respondents as intervention group and 50 respondents as control group). Samples were taken using purposive sampling method. The data was analyzed using t dependent test. Result: The result of the research shows that SEFT can reduce blood sugar levels of the type 2 DM patients with the value of p =0.000, and there was 220.060 points of blood sugar level reduction Conclusion: Nurses should teach type 2 DM patients to do SEFT; to monitor the blood sugar levels before and after SEFT.